BIROKRASI DAN KEDAMAIAN SOSIAL Revitalisasi Birokrasi dalam Resolusi Damai Konflik Sosial - Suradi, Suradi (Sosio Informa : Kajian Permasalahan Sosial dan Usaha Kesejahteraan Sosial, 2007)
Conflict as a social phenomena is never ending in human history. Moreover for the plurality in Indonesian people, conflict is a potential condition as a trigger to social conlict. In Sociologist, the factor of social conflict are caused by treatened for the resource access, basic human right among the people, or maybe people and the government. Conflict social among people and government could be happened since the public policy and development program didn’t have affirmative action to community welfare. Thus we need government bureaucracy revitalitation to reform the model and development approach to the community welfare, for arising social peaceful life. Key word : social conflict, bureaucracy, social peaceful.